2021
DOI: 10.1088/1755-1315/938/1/012005
|View full text |Cite
|
Sign up to set email alerts
|

Feed additive for quails based on fermented brewer’s spent grain

Abstract: The paper discusses the effect of a newly developed complex feed additive Grainbiosorb used in complete feed on livability, age of first egg laying, egg productivity, and feed consumption for the production of 1 dozen eggs of laying quails of the Texas white broiler breed. The scientific experiment was carried out in the experimental vivarium of Krasnodar Research Centre for Animal Husbandry and Veterinary Medicine according to the standard technique recommended by the Federal Scientific Center “All-Russian Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The addition of sand in pullets diets containing brewers dried grains enhanced digestibility, gain, and feed conversion ratio, while the inclusion of higher levels than 15-20% decreased feed conversion efficiency [206]. Fermented brewer's spent grains incorporation in laying quail diets increased gross egg production, the intensity of egg production, and reduced feed conversion ratio [207]. Furthermore, feeding coarse brewer's spent grain instead of ground to broilers feed increased feed utilization and gizzard weight with apparent metabolizable energy and ileal digestibility not being affected [208].…”
Section: Other Agro-industrial By-productsmentioning
confidence: 99%
“…The addition of sand in pullets diets containing brewers dried grains enhanced digestibility, gain, and feed conversion ratio, while the inclusion of higher levels than 15-20% decreased feed conversion efficiency [206]. Fermented brewer's spent grains incorporation in laying quail diets increased gross egg production, the intensity of egg production, and reduced feed conversion ratio [207]. Furthermore, feeding coarse brewer's spent grain instead of ground to broilers feed increased feed utilization and gizzard weight with apparent metabolizable energy and ileal digestibility not being affected [208].…”
Section: Other Agro-industrial By-productsmentioning
confidence: 99%
“…Numerous studies (Gayirbegov et al, 2017;Smolovskaya et al, 2023) and practices show that the productivity, growth, and development of poultry, including quails, are largely determined by feeding conditions. When feeding quails, it is of great importance to enrich their diets with various feed additives of Russian and foreign production (Yurina et al, 2021;Arif et al, 2022). Thus, research (Gayirbegov et al, 2018;Bagno et al, 2019) has found that optimization of the composition of quail feed additives such as M-feed and Calendula officinalis extract improves metabolism and egg productivity.…”
Section: Introductionmentioning
confidence: 99%